TRANSFORMASI PENGELOLAAN LEMBAGA PENDIDIKAN MELALUI FORMULASI STRATEGI: STUDI KASUS YAYASAN SOSIAL DAN PENDIDIKAN BINA MUDA CICALENGKA - Fathur Alhadian; Faoziah Ulfah Fatmawati (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2024)
Education significantly contributes to the quality of human resources in a country. However, Indonesia currently faces educational challenges, with uneven quality and quantity across institutions. Therefore, strategic planning is crucial to enhance education quality at all levels. This study aims to formulate strategies for improving the management of Yayasan Sosial dan Pendidikan Bina Muda Cicalengka. Employing a qualitative and quantitative approach, the research utilizes SWOT and QSPM methods. The findings yield eight consecutive alternative strategies: 1) Developing collaborations and partnerships to enhance internal quality and funding sources, 2) Improving the competence and qualifications of human resources according to national standards, 3) Establishing policies and technical standards for educational management through an integrated information system 4) Enhancing motivation, discipline, and work ethic among human resources, 5) Optimizing information technology for monitoring educational institution performance, 6) Improving educational facilities, 7) Efficiently allocating budget plans, and 8) Enhancing socialization and promotion to boost the institution's reputation in the community. This study's limitation lies in its sole focus on enhancing organizational capacity from an internal perspective. Therefore, future research could delve into external aspects or a combination of both and utilize the Five Forces Porter's analysis method as its analytical tool.